Invasive aspergillosis in adult patients in Australia and New Zealand: 2017-2020Research in context - Shio Yen Tio; Sharon C.-A. Chen; Kate Hamilton; Christopher H. Heath; Alyssa Pradhan; Arthur J. Morris; Tony M. Korman; Orla Morrissey; Catriona L. Halliday; Sarah Kidd; Timothy Spelman; Nadiya Brell; et al. (Elsevier, 2023)
Summary: Background: New and emerging risks for invasive aspergillosis (IA) bring the need for contemporary analyses of the epidemiology and outcomes of IA, in order to improve clinical practice. Methods: The study was a retrospective, multicenter, cohort design of proven and probable IA in adults from 10 Australasian tertiary centres (January 2017-December 2020). Descriptive analyses were used to report patients' demographics, predisposing factors, mycological characteristics, diagnosis and management. Accelerated failure-time model was employed to determine factor(s) associated with 90-day all-cause mortality (ACM). Findings: Of 382 IA episodes, 221 (in 221 patients) fulfilled inclusion criteria - 53 proven and 168 probable IA. Median patient age was 61 years (IQR 51-69). Patients with haematologic malignancies (HM) comprised 49.8% of cases. Fifteen patients (6.8%) had no pre-specified immunosuppression and eleven patients (5.0%) had no documented comorbidity. Only 30% of patients had neutropenia. Of 170 isolates identified, 40 (23.5%) were identified as non-Aspergillus fumigatus species complex. Azole-resistance was present in 3/46 (6.5%) of A. fumigatus sensu stricto isolates. Ninety-day ACM was 30.3%. HM (HR 1.90; 95% CI 1.04-3.46, p = 0.036) and ICU admission (HR 4.89; 95% CI 2.93-8.17, p < 0.001) but not neutropenia (HR 1.45; 95% CI 0.88-2.39, p = 0.135) were associated with mortality. Chronic kidney disease was also a significant predictor of death in the HM subgroup (HR 3.94; 95% CI 1.15-13.44, p = 0.028). Interpretation: IA is identified in high number of patients with mild/no immunosuppression in our study. The relatively high proportion of non-A. fumigatus species complex isolates and 6.5% azole-resistance rate amongst A. fumigatus sensu stricto necessitates accurate species identification and susceptibility testing for optimal patient outcomes. Funding: This work is unfunded. All authors' financial disclosures are listed in detail at the end of the manuscript.